Pengaruh Model Pembelajaran Two Stay to Stray (TS-TS) Oleh Guru PAK Terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 3 Lintong Nihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Elisabeth Syalom Hutauruk; Johari Manik; Oktober Tua Aritonang (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to find out whether there is a positive and significant influence of the Two Stay Two Stray (TSTS) learning model on the learning motivation of class VIII students at SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan district for the 2023/2024 academic year. The method used in this research is a quantitative research method with a pre-experimental design research type in the form of "One Shot Case Study". The population was 177 students from class VIII of SMP Negeri 3 Lintong Nihuta for the 2023/2024 academic year and a sample of 32 people was determined using a purposive sampling technique. Data was collected using an observation sheet with 19 items for variable SMP Negeri 3 Lintong Nihuta, Humbang Hasundutan district, 2023/2024 academic year: 1) Test analysis requirements: a) Test a positive relationship, the value of rxy = 0.595 > rtable(=0.05,n=32) = 0.349. b) Testing a significant relationship obtained a value of tcount= 4.050 > ttable(=0.05,dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="7.36"+0.29X. b) Regression coefficient of determination test (r2) = 35.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=8, dk denominator=n-2=32-2=30) namely 16.36 > 2.27. Thus Ha is accepted and H0 is rejected.